Land your dream career in college : the complete guide to success - Terhune, Tori Randolph; Hays, Betsy A. (Rowman & Littlefield, 2015)
It is clear that the path from college to work has changed dramatically in recent years-current statistics show that half of young college graduates are either jobless or underemployed in positions that don't fully use their skills and knowledge. But landing a good job is not impossible! Authors Tori Randolph Terhune, a gainfully-employed young college graduate herself, and Betsy A. Hays, a college professor, show readers what they can do in college to successfully pave the way for future employment. The authors provide eleven easy-to-follow strategies for students to effectively use time on campus to start building a career.